Enhancing Safety and Durability of AlMgSi Research Reactor Material through Plasma Nitriding: Peningkatan Keamanan dan Daya Tahan Material Reaktor Riset AlMgSi melalui Nitridasi Plasma - Pribadi, Bangun; Priyantoro, Dwi; Lutfi , Shokhul; Sujitno , Tjipto (Universitas Muhammadiyah Sidoarjo, 2023)
This study focuses on enhancing the safety and durability of AlMgSi, a research reactor fuel cladding/structural material, through surface hardening using the plasma nitriding method. The goal is to improve the material's resistance to corrosion while maintaining its integrity under nuclear reactor conditions. AlMgSi samples were nitrided at 448 K for varying times, and the workpiece with the highest surface hardness underwent corrosion and composition tests. The results demonstrated a significant increase in surface hardness by 49% (from 62.35 VHN to 92.79 VHN) and a notable reduction in corrosion rate by 69% (from 11.22 mpy to 3.51 mpy) after plasma nitriding for 3 hours at 448 kelvin. Highlights: Significantly improved surface hardness: Plasma nitriding at 448 K for 3 hours resulted in a remarkable 49% increase in surface hardness, enhancing the material's resistance to wear and deformation. Effective corrosion protection: The plasma-nitrided AlMgSi exhibited a notable 69% decrease in corrosion rate, ensuring the material's longevity and safety under harsh reactor environments. Enhanced nitrogen content: The nitrogen content in AlMgSi increased from 0 to 5.13% atoms after the nitriding process, contributing to the material's improved mechanical and chemical properties.